The City Global Region for the economic and social development of Latin America. - Vargas-Mendoza, Fernando (AiBi Journal of Research, Administration and Engineering, 2020)
The natural consequence that has generated the mutation of the industrial and commercial capitalist system in the macrotechnological, financial capitalism model is the globalization of the goods and services markets. It is an irreversible mega trend, the genesis of the emergence of the Global City Region in which lies a neo-economic and social development approach of the nations, whose analysis as a proposal for Latin America, focuses on the objective of this article. The Global Region, City and the Global Cities are assumed as the key transformation trend to lead the agglomerated cities of Latin America to make the countries an active part of the globalization of the markets, with the possibility that these cities will generate wealth and economic growth with social equity. An interpretive approach to investigation is developed, under the qualitative paradigm, with bibliographic design and explanatory level. The basic technique for the collection of information is the documentary review, based on an average of 40 multinational research referents, of an epistemological and methodological nature. The transversal method of analysis is the critical analysis with hermeneutical approach and heuristic production. It is concluded that if the cities of large Latin American conglomerates do not transform quickly into Global Cities or Global Region Cities; The great dynamics of the process of maturation of global financial capitalism will cause these cities to be exposed to the new models of technological, economic and social and cultural colonization over the next three decades.